Inversion of the Vδ1 to Vδ2 γδ T cell ratio in CVID is not restored by IVIg and is associated with immune activation and exhaustion. Issue 30 (July 2016) - Paquin-Proulx, Dominic; Barsotti, Nathália Silveira; Santos, Bianca A. N.; Marinho, Ana Karolina B. B.; Kokron, Cristina M.; Carvalho, Karina I.; Barros, Myrthes T.; Kalil, Jorge; Nixon, Douglas F.; Kallas, Esper G.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Common variable immunodeficiency (CVID) is defined by low levels of IgG and IgA, but perturbations in T cells are also commonly found. However, there is limited information on γδ T cells in CVID patients. Newly diagnosed CVID patients (n = 15) were enrolled before and after intravenous IgG (IVIg) replacement therapy. Cryopreserved peripheral blood mononuclear cells were then used to study γδ T cells and CVID patients were compared to healthy controls (n = 22). The frequency and absolute count of Vδ1 γδ T cells was found to be increased in CVID (median 0.60% vs 2.64%, P  <0.01 and 7.5 vs 39, P  <0.01 respectively), while they were decreased for Vδ2 γδ T cells (median, 2.36% vs 0.74%, P  <0.01 and 37.8 vs 13.9, P  <0.01 respectively) resulting in an inversion of the Vδ1 to Vδ2 ratio (0.24 vs 1.4, P  <0.001). Markers of immune activation were elevated on all subsets of γδ T cells, and HLA-DR expression was associated with an expansion of Vδ1 γδ T cells ( r  = 0.73, P  = 0.003). Elevated PD-1 expression was found only on Vδ2 γδ T cells (median 1.15% vs 3.08%, P  <0.001) and was associated with the decrease of Vδ2 γδ T cells ( r  = −0.67, P  = 0.007). IVIg had no effect on the frequency of Vδ1 and Vδ2 γδ T cells or HLA-DR expression, but alleviated CD38 expression on Vδ1 γδ T cells (median MFI 965 vs 736, P  <0.05). These findings suggest that immunological perturbations of γδ T cells are a general feature associated with CVID and are only partially reversed by IVIg therapy.